KATEGORI FATIS DALAM NOVEL DILAN 1990 KARYA PIDI BAIQ - Pratiwi, Melsi Rahayu; Agustina, Agustina (Jurnal Bahasa dan Sastra, 2019)
Â This study aims to describe (1) the form of the fatist category and (2) the fatist category function in the Dilan 1990 novel by Pidi Baiq. This type of research is qualitative research using descriptive analysis methods.The research data is in the form of sentences containing phatic categories in the Dilan 1990 novel by Pidi Baiq. Methods and techniques of data collection using tapping techniques. Data collection techniques are carried out by identifying data based on the form and function of the fatist category.Based on the results of the research and discussion, it can be concluded that the phatic categories in the Dilan 1990 novel by Pidi Baiq are as follows (1) the form of phatic category is found in four forms, namely phatic particles, phatic words, phobic phrases, and phytic alloys; (2) the phatic category function is found in fourteen functions, namely emphasizing the feeling of rejection; emphasize certainty; request approval from the interlocutor; just emphasis in the sentence; smoothing orders; as confirmation; start and end the conversation; emphasize proof; emphasize reason and denial; emphasize invitation; justify the statement of the interlocutor; give approval to friends to talk; after getting something from friends talking; and replace the question word why or why.Â Keywords: fatis, form, function, novelÂ